Evaluasi Produksi Alat Mekanis pada Unit Crushing Plant di PT TOP Kabupaten Mempawah Kalimantan Barat - Firman (Journal of Applied Mechanical Engineering and Renewable Energy, 2022)
TOP is a mining company in granodiorite located in Mempawah Regency with a production target of 150 tons per day. Mining activities are carried out by blasting which are transported using a Dump Truck to be sent to the Crushing Plant unit to be processed according to size. The processing of granodiorite in the Crushing Plant unit consists of two stages, namely Primary crushing and Secondary crushing. The tools used are 1 unit of primary crushing (Jaw Crusher) and 1 unit of Secondary crushing (Cone Crusher). The use of crushing equipment is supported by equipment such as hoppers, feeders, screening and belt conveyors. This series of processing produces production in the form of stone ash, 1x1 mm, 1x2 mm, and 0.5 mm. The purpose of this activity is to evaluate the achievement of granodiorite production targets at PT. TOP and knowing the factors that hinder the performance of the crushing plant tool. The results of the evaluation of production on belt conveyors 11,12,13, and 14 are in accordance with the production target at PT. TOP, but the production target is not optimal. For this reason, the company can increase production targets without add a belt conveyor to the Crushing Plant unit. while the factors that hinder the performance of the crushing plant are the slow handling of the damaged crushing plant machine, the material size is too large.